As temáticas de pesquisa da geografia agrária nas dissertações e teses dos programas de pós-graduação em geografia na região sudeste - Ferreira, Darlene Aparecida de Oliveira [UNESP]; Valle, Maria Ribeiro do [UNESP]; Pessôa, Vera Lúcia Salazar; Romanatto, Maria José; Marafon, Glaucio José (My University, 2014)
The purpose of this joint effort involving professors/researchers of Southeast Brazilian un iversities was to dentify the theoretical bases, categories and logical principles of what might now be referred to as Rural Geography. To achieve that a survey was conducted of the dissertations and theses submitted between 1970 and 2009 to the graduate Geography programs of UFMG and UFU in the state of Minas Gerais, of UFRJ, UFF and UERJ in Rio de Janeiro and of USP, UNESP Rio Claro and UNESP Presidente Prudente in São Paulo. The information gathered allows us to suggest that these Programs played a significant role in the development of Rural Geography in Brazil by training teachers/professors, fostering studies on Brazil’s farming sector and disseminating the theoretical propositions that underlie these studies, which should be further examined in the future.

A proposta foi realizar um trabalho conjunto, envolvendo professores pesquisadores das Universidades da região Sudeste, que identificasse quais os referenciais teóricos, as categorias e os princípios lógicos do que se poderia chamar hoje de Geografia Agrária. Para cumprir com o objetivo proposto realizou-se levantamento de dissertações e teses, defendidas entre 1970 e 2009, nos Programas de Pós-Graduação em Geografia da UFMG e UFU em Minas Gerais; UFRJ, UFF e UERJ no Rio de Janeiro; e na USP, UNESP Rio Claro e UNESP Presidente Prudente em São Paulo. O conjunto das informações levantadas permitiu apontar que os Programas estudados tiveram uma articipação significativa no desenvolvimento da Geografia Agrária brasileira, formando docentes, incentivando estudos sobre o setor agropecuário no Brasil e disseminando proposições teóricas sustentadoras dos estudos realizados a serem futuramente analisadas.
Research themes in master’s and doctoral theses in rural geography from southeast brazilian graduate geography programs
Keywords: Rural Geography; Graduate Programs; Southeast Brazil; Geografia Agrária; Programas de Pós-Graduação; Região Sudeste